ASEAN, SAARC, and the indomitable China in food trade: A gravity model analysis of trade patterns - Ajmani, Manmeet Singh; Choudhary, Vishruta; Kishore, Avinash; Roy, Devesh (International Food Policy Research Institute, 2020)
We assess food trade among and across two Asian trading blocs, the Association of Southeast Asian Nations (ASEAN) and the South Asian Association for Regional Cooperation (SAARC), and China. Using most recent innovations in the empirical trade model, we find subpar trade for several countries but some over-trading as well, likely driven by weak economic fundamentals determining trade. Further, we find that Bangladesh, Philippines, Sri Lanka, and Viet Nam under-export to China, and to nearly all ASEAN and SAARC countries, with the magnitude varying between 40 and 100 percent below the predicted trade levels. While checking for competing explanations, we identify trading pair time variant factors such as tariffs reducing the magnitude of under-exporting of ASEAN and SAARC countries by 1 and 3 percent, respectively. We also highlight unobserved variables such as trust between countries as factors important for strong agricultural trade.